2010
DOI: 10.1007/s10551-010-0658-z
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation, Corporate Social Responsibility, and Business Performance

Abstract: market orientation, corporate social responsibility, resource-based view, Dubai, emerging economies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(79 citation statements)
references
References 101 publications
(120 reference statements)
5
73
1
Order By: Relevance
“…A multifaceted approach to prosocial activity contributes to the fact that in an organisation's analysis an abandonment of perceiving it as a source of benefits for investors, earnings for employees and products for consumers takes place, and then there is a shift to an organisation's analysis as corresponding to social and environmental needs and values (Adamus-Matuszyńska, 2013;Hediger, 2010). Concrete social obligations are contained in basic social requirements and in qualitative programmes of an organisation (Brik, Rettab & Mellahi, 2011;Maignan & Ferrell, 2004;Pratley, 1995): towards broadly understood expectations of customers, towards a society in use of environmental resources area, towards the employed in terms of ensuring adequate working conditions. The objectives implemented within the framework of qualitative programmes incorporate ,in the author's opinion, apart from basic quality requirements also preventing unnecessary damage, improving operational processes and building durable partnership with stakeholders.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A multifaceted approach to prosocial activity contributes to the fact that in an organisation's analysis an abandonment of perceiving it as a source of benefits for investors, earnings for employees and products for consumers takes place, and then there is a shift to an organisation's analysis as corresponding to social and environmental needs and values (Adamus-Matuszyńska, 2013;Hediger, 2010). Concrete social obligations are contained in basic social requirements and in qualitative programmes of an organisation (Brik, Rettab & Mellahi, 2011;Maignan & Ferrell, 2004;Pratley, 1995): towards broadly understood expectations of customers, towards a society in use of environmental resources area, towards the employed in terms of ensuring adequate working conditions. The objectives implemented within the framework of qualitative programmes incorporate ,in the author's opinion, apart from basic quality requirements also preventing unnecessary damage, improving operational processes and building durable partnership with stakeholders.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, many researchers have identified a number of variables believed to impact how a firm's social performance relates to its financial performance (Andersen & Dejoy, 2011). Callan and Thomas (2009) found that control variables must be properly specified to avoid bias and that some measures are related to CFP.…”
Section: Different Control Variablesmentioning
confidence: 99%
“…The first category is based on consumers, which mostly relate with product quality, diversity, product safety, quality of services, innovativeness, alcohol, tobacco, gambling and nuclear power (Preston, O'Bannon, 1997; Mahoney, Roberts, 2007;Moore, 2001, etc.). The second category is based on government, community or military, such as governments, community investment, community relations, community and society, defense/weapons, military contracting ( Brik, Rettab, Mellahi, 2011;Andersen and Dejoy, 2011;Surroca, Tribo, 2005;Fauzi, 2009;Baron, Harjoto and Hoje Jo, 2011,et.). The third category is based on employee, such as employees, human right, labor relations, ability to attract\develop and keep talented people (Fauzi et al 2007;Laan et al 2008;Waddock and Graves, 1997, et.).…”
Section: Various Stakeholder Groupsmentioning
confidence: 99%
See 2 more Smart Citations